Rock geochemistry induces stress and starvation responses in the bacterial proteome. (22nd December 2015) - Bryce, Casey C.; Le Bihan, Thierry; Martin, Sarah F.; Harrison, Jesse P.; Bush, Timothy; Spears, Bryan; Moore, Alanna; Leys, Natalie; Byloos, Bo; Cockell, Charles S.
Summary: Interactions between microorganisms and rocks play an important role in Earth system processes. However, little is known about the molecular capabilities microorganisms require to live in rocky environments. Using a quantitative label‐free proteomics approach, we show that a model bacterium ( C upriavidus metallidurans  CH34) can use volcanic rock to satisfy some elemental requirements, resulting in increased rates of cell division in both magnesium‐ and iron‐limited media. However, the rocks also introduced multiple new stresses via chemical changes associated with pH, elemental leaching and surface adsorption of nutrients that were reflected in the proteome. For example, the loss of bioavailable phosphorus was observed and resulted in the upregulation of diverse phosphate limitation proteins, which facilitate increase phosphate uptake and scavenging within the cell. Our results revealed that despite the provision of essential elements, rock chemistry drives complex metabolic reorganization within rock‐dwelling organisms, requiring tight regulation of cellular processes at the protein level. This study advances our ability to identify key microbial responses that enable life to persist in rock environments.